Radicalisms, violence and political integration in Turkey - Bozarsian, Hamit (Tempo Social, 2001)
This article analyses the main obstacles to be faced for the political integration in Turkey. It shows that radicalism and violence spring from three sources; the Turkish-Kurd opposition; the Sunite-Alevite opposition and the rise of political Islamism, with its refusal to abandon religious reference.What has contributed to the present political fragmentation are the contradictions of the Kemalist doctrine, on which the legitimacy of the Turkish State is based; the successive military coups d'etat that cause constant party realignements; and the militarization of vast regions of Turkey to hold back the successive waves of Kurdish and Alevite violent uprisings, which, in turn, give autonomy to armed groups that tend to perpetuate the violent contends and repression. From this perspective, the future of Turkey depends, on the one hand, on the social integration of identifications and convictions (Kurds, Alevites and Islamites) for the recognition of regional cultures and, on the other, on the adoption of the principle of non-politization of religious convictions and the abandonment of social conservatism as an opposition to westernization.